(untitled) (Baghdad Science Journal, 2022)
The current study was conducted for studying the impact of cold plasma on the expression level of three genes that participate in the biosynthesis of the phenylpropanoid pathway in Ocimum basilicum. These studied genes were cinnamate 4-hydroxylase (c4h), 4-coumarate CoA ligase (4cl), and eugenol O-methyl transferase (eomt). Also, the cold plasma impact was studied on the essential oil components and their relation with the gene expression level. The results demonstrated that cold plasma seeds germination of the treated groups 2 (initially for 3 minutes and 3 minutes after 7 days) ,and group 3(initially for 5 minutes and 3 minutes after 7 days) were faster than the control group. Also, the height average of the mature plants of groups 2and 3 was between (50 to73), (50 to 100) cm, respectively compared to the control group which was (40 to 70cm). Moreover, the results indicated significant differences (P-value ≤0.01) in the level of gene expression, which increased for the c4h, 4cl, and eomt genes in group 2 about (5.63 ±0.39), (3.42 ±040) ,and (5.41±0.23) folds respectively compared with untreated control. Additionally, the level of gene expression increased for the c4h, 4cl, and eomt genes in group 3 about (42.34 ±049), (4.13 ±0.38), and (6.29 ±0.71) folds compared with untreated control(1.00 ±0.00) folds.Concerning the contents of essential oil for the control group, group 2, and group 3 were 0.434%, 0.713, and 0.792% (v/w) respectively. Moreover, the general composition of the essential oil in the examined sweet basil, phenylpropanoids was the eugenol compound and its derivatives for the control group, group 2, and group 3 which were 2.76%, 8%, and 11% (v/w) respectively. We concluded that the atmospheric cold plasma has shown an effect on gene expression and essential oil content of phenylpropanoid compounds in Ocimum basilicum L. cultivated in Iraq, as the essential oil contents have important therapeutic properties.